Improving Students' Listening Skill by Using Role-Play Method in the Material of Asking for and Giving Directions - Widiyastuti, Windy; Setyowati, Titik; Wiyaka, Wiyaka (Jurnal Pendidikan Guru Profesional, 2023)
A communication strategy that enables listeners to comprehend what is said is referred to as listening skills. This enables effective communication to be established as well. This research aimed to improve listening skills in class VII F students of SMPN 6 Semarang for the 2022/2023 academic year in learning English with the material "asking for and giving directions" using the role-playing method. The research design uses Kemmis and Mc. Taggart. This classroom action research was carried out in 2 cycles. The time used for each cycle is 2 meetings with 2 material presentation meetings, and at the end of the second meeting, a cycle evaluation is held. Each cycle has 4 stages: planning, action, observation, and reflection. The number of students involved in this study was 34 students. Data collection techniques using observation and questionnaires. Data were analyzed descriptively and presented in the form of tables and graphs. The results showed increased students' listening scores on the material "asking for and giving directions". Namely, in the first cycle, 32.35% of students were able to exceed the KKM, and then in the second cycle, it increased to 61.76% of students were able to exceed the KKM. Thus, the role-playing method can improve student learning outcomes in listening activities and "asking for and giving directions" for class VII F students of SMPN 6 Semarang.